2010
DOI: 10.1590/s1413-73722010000100010
|View full text |Cite
|
Sign up to set email alerts
|

O crime passional na perspectiva de infratores presos: um estudo qualitativo

Abstract: RESUMO. O objetivo desta pesquisa foi apreender aspectos emocionais ligados ao crime passional, à vivência carcerária dos infratores presos por este delito e seus efeitos. A análise qualitativa dos prontuários e de entrevistas realizadas em duas penitenciárias de Salvador/BA deu-se a partir de categorias apreendidas nas narrativas. Verificou-se que os criminosos, ao se envolverem num relacionamento amoroso e se depararem com um rival ou uma situação de traição, ficam mobilizados pelos sentimentos de ciúme, amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…One study on crimes of passion, undertaken with those who had committed them and who were in prison, revealed that the motivation for homicide was betrayal on the part of the women. 25 One study performed with HIV-positive men in Ribeirão Preto, São Paulo, Brazil, shows that women who have extraconjugal relationships are vulnerable to the experience of violence, and calls attention to the fact that this female infidelity may be imaginary. 26 In this regard, the conjugal violence is manifested not only because of the woman's betrayal, but also because of suspicion of this, even when this is baseless.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One study on crimes of passion, undertaken with those who had committed them and who were in prison, revealed that the motivation for homicide was betrayal on the part of the women. 25 One study performed with HIV-positive men in Ribeirão Preto, São Paulo, Brazil, shows that women who have extraconjugal relationships are vulnerable to the experience of violence, and calls attention to the fact that this female infidelity may be imaginary. 26 In this regard, the conjugal violence is manifested not only because of the woman's betrayal, but also because of suspicion of this, even when this is baseless.…”
mentioning
confidence: 99%
“…The consumption of alcoholic drinks by the partners is one of the main causes leading the partner to commit crime. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Attention is also called to the fact that the women state that the use of drugs/alcohol is the event causing conjugal violence, it being considered that if this is absent, the conjugal relationship is healthier. The women studied declared that when their partners drink, they are transformed, attacking them, initially verbally, and then progressing to other types of violence.…”
mentioning
confidence: 99%
“…Therefore, once manifested in the individual, jealousy awakes the need of possessing and keeping the loved one. Such situation demands permanent presence and leads the "jealous" subject to demonstrate intolerance with the other person (9) . Therefore, jealousy is understood as a reaction that appears when affective stability is threatened by a rival, whatever the cause may be.…”
Section: Resultsmentioning
confidence: 99%
“…Coulouris (2004) ao ciúme e ao uso de álcool e drogas. Essa afirmação está de acordo com a literatura, pois resultados de uma pesquisa mostraram que vários fatores culturais e psíquicos motivam e contribuem para a ocorrência do ato criminoso, dentre eles o patriarcalismo, o machismo, as noções de masculinidade e virilidade, a ideia de defesa da honra, o uso de substâncias psicoativas, os sentimentos de rivalidade, ciúme, amor, ódio e a intolerância à traição (Santiago & Coelho, 2010). Além disso, o uso de álcool pelo marido tem sido frequentemente relacionado com a violência conjugal e que episódios de violência são mais frequentes em casais em que o marido tem problemas com abuso de bebidas alcoólicas e a esposa não (Serafim, Barros & Rigotti, 2006).…”
Section: Discussionunclassified